Development of a Multitype Wireless Sensor Network for the Large-Scale Structure of the National Stadium in China - Yanbin Shen; Pengcheng Yang; Pengfei Zhang; Yaozhi Luo; Yujia Mei; Huaqiang Cheng; Li Jin; Chenyu Liang; Qiaqin Wang; Zhouneng Zhong (International Journal of Distributed Sensor Networks)
A multitype wireless sensor network (WSN) for structural health monitoring is developed for the National Stadium in China (generally known as “Bird's Nest”). The stadium is a super large-scale building built for the 2008 Beijing Olympic Games and can house more than 90,000 occupants. The structure is very rigid and weighs more than 40,000 tons in total. Considering the structural features and on-site environment, the system takes multitype sensors as measurement components including stress, displacement, acceleration, wind, and temperature. The monitoring module design consists of four functions: sensing, processing, wireless communication, and energy management. The communication between each sensor node is realized by using an adjustable and artificial-control chain-type network. A total of 290 sensors were installed on the structure, and the data collection work has been carried out for more than one year. This paper mainly focuses on the system development and project application, while the data analysis work is briefly discussed as well. It can be concluded that the customized WSN is robust and durable, which well satisfies the requirement of plenty multitype sensors working in a large-area distribution. The data analysis results reveal that the super large-scale structure is very sensitive to the temperature effect.